Income and Occupational Intergenerational Mobility in New Zealand - Matthew Gibbons (New Zealand Government, The Treasury, 2010)
Intergenerational mobility research quantifies the relationship between the circumstances of parents and the circumstances of their children as adults. This paper tentatively quantifies intergenerational economic mobility in New Zealand using the best available datasets. These datasets are: longitudinal income data from the Dunedin Study of the population of people born in Dunedin in 1972-73; and occupation data from the 1996 Election Study's post-election nationwide survey. The occupation data determines the Socio-Economic Status (SES) of respondents and their parents. The results show that only a small proportion of variance in income or SES was explained by the economic situation of people's parents, indicating that other explanatory variables are more important. The Dunedin Study results suggest that rates of intergenerational income mobility for men and women from Dunedin are probably within a similar range to rates of intergenerational income mobility in most other developed countries. Our results provide weak evidence that New Zealand has higher intergenerational occupational mobility than Britain, and stronger evidence that New Zealand men have higher intergenerational occupational mobility than men in Germany. Unfortunately, insufficient data is available to make intergenerational occupational mobility comparisons with other countries. We have to be cautious when interpreting our results because both datasets we used contain proportionately fewer Maori and Pacific peoples than New Zealand's population. The Dunedin Study was founded in a single city, and while the study has a very high participation rate its participants may not be fully representative of New Zealand's population. In addition, participants have not reached their peak earning years, and this may have affected the results. The nationwide Election Study is under-representative of people from groups less likely to be on the electoral roll and the data is now over 14 years old.
Keywords: J62; F22; 330; Social mobility; Emigration; Soziale Mobilität; Lohnniveau; Generationengerechtigkeit; Australien